2004
DOI: 10.1128/mcb.24.3.1188-1199.2004
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 Controls the Activity of the Retinoblastoma Protein via Regulation of p21CIP1/WAF1/SDI

Abstract: The ubiquitous mammalian chromatin-remodeling SWI/SNF-like BAF complexes play critical roles in tumorigenesis. It was suggested that the direct interaction of BRG1 with the retinoblastoma protein pRB is required for regulation of cell cycle progression by pRB. We present evidence that the BRG1-containing complexes regulate the expression of the cdk inhibitor p21 CIP1/WAF1/SDI . Furthermore, we show that the physical interaction between BRG1 and pRB is not required for induction of cell growth arrest and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 76 publications
5
84
4
1
Order By: Relevance
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our data suggest that BRG1 silencing altered the homeostasis of DNA repair pathway. In fact, the H2AX activation and the upregulation in the expression BRG1, RB and P53 crosstalk Several reports suggested that BRG1 binds to and regulates the retinoblastoma protein and the tumor suppressor protein p53 (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). These are master genes that control cell cycle arrest, differentiation, apoptosis and/or senescence (Felsani et al, 2006;Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007).…”
Section: Genes Involved In Dna Repairmentioning
confidence: 99%
“…However, restoration of BRG1 or BRM expression reconstitutes RB growth inhibition in such cells. SWI/SNF is required for E2F-dependent transcription (Trouche et al, 1997;Kang et al, 2004;Liu et al, 2004), although all of the effects of SWI/SNF on RB checkpoint control may not require binding of BRM or BRG1 to RB. For example, re-expression of BRG1 induces p21, which inhibits RB phosphorylation by cyclin dependent kinases (CDKs) (Kang et al, 2004).…”
mentioning
confidence: 99%
“…SWI/SNF is required for E2F-dependent transcription (Trouche et al, 1997;Kang et al, 2004;Liu et al, 2004), although all of the effects of SWI/SNF on RB checkpoint control may not require binding of BRM or BRG1 to RB. For example, re-expression of BRG1 induces p21, which inhibits RB phosphorylation by cyclin dependent kinases (CDKs) (Kang et al, 2004). Cyclin E has been shown to bind and, in conjunction with CDK2, phosphorylate BRG1 and BAF155 (Shanahan et al, 1999;Brumby et al, 2002).…”
mentioning
confidence: 99%
“…5), homologous to a conserved domain of a chromosome-remodeling factor BRG1-associated protein, structurally capable of binding to p53 at the MDM2-binding site (36). BRG1 and its associated factors are known to form a repressor complex that restricts cyclin A expression until released by cyclin E in a cell cycle-dependent fashion (22,37). The tumor suppressor p53 binds with BRG1 and several components of this repressor complex to up-regulate p21 expression (38,39).…”
Section: Elimination Of Mdm2 Expression Elevates Endogenous Cyclin a mentioning
confidence: 99%